Upper limb joint kinetic analysis during tennis serve: Assessment of competitive level on efficiency and injury risks - Martin, C.; Bideau, B.; Ropars, M.; Delamarche, P.; Kulpa, R. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The aim of this work was to compare the joint kinetics and stroke production efficiency for the shoulder, elbow, and wrist during the serve between professionals and advanced tennis players and to discuss their potential relationship with given overuse injuries. Eleven professional and seven advanced tennis players were studied with an optoelectronic motion analysis system while performing serves. Normalized peak kinetic values of the shoulder, elbow, and wrist joints were calculated using inverse dynamics. To measure serve efficiency, all normalized peak kinetic values were divided by ball velocity. t-tests were used to determine significant differences between the resultant joint kinetics and efficiency values in both groups (advanced vs professional). Shoulder inferior force, shoulder anterior force, shoulder horizontal abduction torque, and elbow medial force were significantly higher in advanced players. Professional players were more efficient than advanced players, as they maximize ball velocity with lower joint kinetics. Since advanced players are subjected to higher joint kinetics, the results suggest that they appeared more susceptible to high risk of shoulder and elbow injuries than professionals, especially during the cocking and deceleration phases of the serve.